ANALISIS USAHA PEMBUATAN TEMPE (Studi Kasus pada Usaha Pembuatan Tempe “Bapak Joko Sarwono”) DI KELURAHAN BINUANG KECAMATAN BINUANG KABUPATEN TAPIN - Hairun Hairun; Suslinawati Suslinawati; Ana Zuraida (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The aim of research to know technically Enterprises Making Tempe Mr. Joko Sarwono and to find out the revenue costs, benefits and feasibility of making tempeh as well as the problems faced in Tempe Making Enterprises factory. The data collected is in the form of primary and secondary data. Primary data was collected through direct interviews with entrepreneurs tempe, using questions that have been prepared beforehand. Results of research on Analysis of Business making tempe in Subdistrict Binuang Tapin district in April 2016 is the amount of average production per day 40 boards tempe with the production value of Rp. 25,000,000, - per month and variable costs of making tempe Rp.19,600,000, - or Rp 784,000, - per day and fixed costs Rp. 3,128,250, - or Rp. 125,130, - per day, for a month tempe reception is Rp.25,000,000, - or Rp 1,000,000, - per day and profits of Rp. 2,271,750,- or Rp. 90,870, - per day so that the value of R / C Ratio obtained for 1.10 means RCR> 1 means the tempe making business profitable and worth the effort. Keywords: Tempe, business analysis, Revenue cost ratio